Tuberculosis: An Interdisciplinary Overview For Laboratory, Nursing, And Epidemiology Practice (The Review of Diabetic Studies, 2024)
Background: Tuberculosis (TB) remains a leading infectious cause of morbidity and mortality worldwide, characterized by complex diagnostic, therapeutic, and preventive challenges. Despite being preventable and curable, TB persists due to biological, social, and systemic factors.Aim: This review aims to provide an interdisciplinary synthesis of TB’s etiology, epidemiology, pathophysiology, diagnostic strategies, treatment approaches, and public health implications for laboratory, nursing, and epidemiology professionals.Methods: A comprehensive literature review was conducted using WHO global reports, CDC guidelines, and peer-reviewed studies to integrate historical and contemporary perspectives on TB biology, clinical management, and control strategies.Results: TB is caused primarily by Mycobacterium tuberculosis, an intracellular pathogen with slow growth and latency potential. Approximately 25% of the global population harbors latent infection, with 10.6 million active cases reported in 2022. Diagnostic challenges persist due to nonspecific symptoms, low bacillary burden, and resource limitations. Advances such as nucleic acid amplification tests (NAATs) and interferon-gamma release assays (IGRAs) have improved detection, yet access remains inequitable. Treatment requires prolonged multidrug regimens; recent innovations include shorter preventive therapy and new drugs for resistant TB. Drug resistance and TB–HIV coinfection remain critical threats.Conclusion: Effective TB control demands integrated strategies combining rapid diagnostics, patient-centered care, and robust public health infrastructure. Interprofessional collaboration is essential to achieve WHO’s goal of 90% incidence reduction by 2035.